Orthodontic intervention to resolve periodontal defects: An interdisciplinary approach - Khurana Priyanka; Soni Vivek (Wolters Kluwer Medknow Publications, 2010)
In the new era of esthetics, Orthodontic therapy has gained tremendous acceptance by adults. However,treating adults is more challenging as they present with multiple periodontal problems compromising orthodontic treatment. Hence, to provide optimal treatment to adult patients an active interaction between orthodontist and periodontist is imperative.This article addresses the dilemmas encountered during the treatment of orthodontic patients with periodontal defects.